Dampak Kebijakan Pendidikan Karakter Terhadap Perilaku Siswa di Sekolah - Shakila Putri Suhara; Tengku Darmansah; Anggi Sofiyana Nasution; Tika Kesuma Wardani (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the impact of character education policies on student behavior in schools. Character education has become a priority in national education policy as an effort to form a generation that has integrity, responsibility, and tolerance. The method used in this study is a literature study, where data is collected from various literature, such as scientific journals, books, and relevant research reports. The results of the analysis show that the implementation of character education policies has a positive impact on student behavior, such as increasing discipline, honesty, and the ability to work together. However, the effectiveness of this policy is influenced by several factors, including the quality of implementation in schools, support from teachers and parents, and a conducive school environment. This study is expected to be a reference for policy makers and education practitioners in optimizing character education programs in schools.